What is a self-made expat? Self-disclosures of self-initiated expatriates - Steffen Roth; Léo-Paul Dana (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The label expatriates is increasingly used by and applied to a growing number of persons who do not fit classical concepts of company-driven expatriation. While relevant research is engaged in establishing interaction with smaller samples of self- initiated expatriates, the present article represents netnography of a larger, international sample of self-designated self-initiated expatriates who, independently of any research intervention, engaged in an online conversation headlined “Self-Made Expats?” on the international expatriates platform internations.com. While key findings from this non- responsive approach to the self-disclosures of an internationally diverse web community of self-made expatriates support certain dimensions of prevailing academic definitions, they also suggest reconsidering the so far disclaimed relevance of entrepreneurialism for the concept of self-initiated expatriation.
Keywords: L26; L31; 330; expatriation; self-made expats; entrepreneurship; netnography; internations.com; Entrepreneurship approach; Career development